KEMAMPUAN INTERPERSONAL ANAK USIA 4-5 TAHUN (PENELITIAN KUALITATIF DI RA ULIL ALBAB, SUKATANI-DEPOK) - Agusni, Debby Fitriani (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
This research aims to see and describe how the interpersonal skills of children aged 4-5 years. This research was conducted in schools Raudhatul Athfal Ulil Albab, Sukatani, Depok. The method that used in this research was qualitative study. Collected data with observation, documentation, and interviews. Research carried out by observing and looking for information on how the interpersonal skills of children aged 4-5 years in RA Ulil Albab. Results showed children 4-5 years in RA Ulil Albab have social communication skills in responding quickly and accurately the intent and desire of their peers, social sensitivity to feel the feeling of peers, so it is able to show empathy, and the ability to understand and find solutions effective problem of the problem that occurred. Social interaction is also seen positive through children able to communicate and cooperate. The results showed that by being able to understand and respond to the intent, desires, and feelings of peers will encourage positive interactions with peers in their neighbourhood.